Minimizing eclipses via synodic resonant orbits with applications to EQUULEUS and MMX. (March 2021) - Chikazawa, Takuya; Baresi, Nicola; Campagnola, Stefano; Ozaki, Naoya; Kawakatsu, Yasuhiro
Abstract: For deep-space missions that remain in the vicinity of a target body, solar eclipses might become a source of major concern due to thermal and power constraints. This paper presents a method for minimizing the eclipse duration of periodic trajectories in three-body systems using synodic resonant periodic orbits. The proposed methodology successfully captures the global eclipse structure of synodic resonant periodic orbits in terms of driving parameters such as elongation and phase angles. Two-dimensional Eclipse maps are introduced to identify optimal orbit insertion conditions that avoid or minimize eclipse intervals. The validity and applicability of the proposed method is tested in the full-ephemeris model (DE430) of the Earth–Moon and Mars–Phobos systems, respectively. As a result of these investigations, we propose new science minimum-eclipse trajectories that are under consideration for the upcoming JAXA missions EQUULEUS and MMX. Highlights: Eclipses have the potential to endanger the safety and operations of space missions. We derive relation between eclipse of periodic orbits and mission design parameters. Minimum eclipse orbits can be achieved through the proposed graphical tool. The validity of developments has been investigated and applied for two JAXA missions.